Uncertainty measurement and regional comparison of the technology transfer process – an empirical study based on data from 30 provinces in China. (17th June 2022) - Qiu, Yingying; Feng, Feng; Zhang, Leiyong; Li, Xingteng
Technology transfer is a stage-by-stage process that is full of uncertainties. This study uses a graphical evaluation review technology (GERT) network to construct an uncertainty measurement model of the technology transfer process. In addition, the science and technology data input from the 30 provinces and autonomous regions of the provinces in China are used to measure the uncertainty associated with technology transfer in each province. It is concluded that the uncertainty associated with technology transfer in China varies from region to region and has a negative correlation with the level of economic development. Thereafter, with the help of construction of uncertainty difference matrix, the policy recommendation is put forward, in which reducing 'target phase' uncertainty can largely promote transformation of science and technology.